Design of a Vibration Instrumentation Device Using an ADXL Accelerometer Sensor on an Arduino-Based Vertical Milling Machine - Rusydi Husaini; Razali (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of the manufacturing industry demands a machining process that has a high level of precision and reliability, so monitoring the condition of the machine is one of the important aspects to maintain the quality of the production process. This study aims to design and test an Arduino Mega 2560-based vibration instrumentation device using an accelerometer sensor ADXL345 to measure vibration in vertical milling machines. The developed system measures vibration acceleration on the X, Y, and Z axes, then calculates the Total Root Mean Square (RMS) value as an indicator of the machine's vibration level. The test was carried out 15 times on a vertical milling machine with the same machining parameters, then the measurement results were compared with the HT-1201 vibration meter as a reference tool. The test results showed that the Total RMS value obtained was in the range of 0.807–1.586 m/s². The validation process resulted in an average error value of 12.95%, and an average accuracy of 87.05%. The results show that the developed tool has a good level of conformity with standard measuring instruments so that it is suitable for use as an alternative to vibration monitoring in vertical milling machines.